Antioxidant studies of cave edible bird’s nest / Noraini Deraman - Deraman, Noraini (Faculty of Applied Sciences, 2012)
Edible bird’s nest (EBN) is well known for its health enhancing effects such as antiaging, growth promoting and immune enhancing properties. This study was performed with the aims to determine the antioxidant activities of cave EBN (Collocalia fuciphaga) and to evaluate the effect of pH (strong acid, mild acid, neutral, mild alkaline and strong alkaline) on the antioxidant activities of cave EBN. The antioxidant activities were analysed by using two in-vitro chemical methods 1,1- diphenyl-2-pycrylhydrazyl (DPPH) free radical scavemging assay and Ferric reducing antioxidant power (FRAP) assay. The cave EBN were extract using citric acid (mild acid), sodium citrate (mild alkaline), HCl (strong acid), NaOH (strong alkaline) and distilled water (neutral). These results indicated that the antioxidatives activities may be dependent on the pH of extraction. The strong acid and strong alkaline extraction of EBN showed higher radical scavenging and reducing power ability. The DPPH and FRAP assay showed positive with strong correlation (r = 0.980). Based on this study, the EBN could be a potential source of natural antioxidants.